Retronucal cystic hygroma as a marker of chromosomal abnormalities in the first trimester of gestation - Update - Huamán Guerrero, Moisés (2022)
Objective: To evaluate the association of retronucal cystic hygroma (RCH) and fetal chromosomal abnormalities. Methods: Retrospective observational study of 323 first trimester fetuses at risk for chromosomal abnormalities diagnosed by ultrasound between 11 and 13.6 weeks. Results: Of 323 fetuses at risk for chromosomal abnormalities, 132 cases of chromosomal abnormalities were found (40.9%). A total of 145 cases of RCH were identified; chorionic villus biopsy was performed in 64 (56.6%) and amniocentesis in 81 (43.5%); an abnormal karyotype was found in 82 (56.6%). Of 88 fetuses with isolated RCH, 33 (37.5%) had some chromosomal abnormality. In 58 fetuses with RCH associated with other abnormal findings, chromosomal abnormalities were found in 43 fetuses (74.1%) and of these 24 (41.4%) had abnormal ductus venosus flow wave (DVF), 17 (29.3%) had generalized edema, 8 cases (13.8%) with cardiopathy, 7 (12,1%) with absent nasal bone. The predictive values of RCH were sensitivity (S) 62.1%, specificity (Sp) 67%, positive predictive value (PPV) 56.6%, negative predictive value (NPV) 71.9%, p<0.001, OR: 3.3. RCH associated with other abnormal findings were S 52.4%, Sp 76.2%, PPV 76.2%, OR: 3.5, LR+: 2.2, p<0.000. Generalized edema and abnormal ductus venosus had the highest predictive values: PPV 88.2% and 83.3%, respectively. The most frequently found chromosomal abnormalities were T21 (53.7%), monosomy X (18.3%), T18 (15.9%), T13 (6.1%). Conclusions: Retronucal cystic hygroma is a risk marker with high predictive value for chromosomal abnormalities, being higher when associated with other abnormal ultrasound findings. Ultrasonographic identification of RCH in first trimester prenatal screening should be an indication to recommend diagnostic testing for chromosomal abnormalities.